Penentuan Nilai LC₅₀ Ekstrak Etanol 80% Daun Trembesi (Samanea saman (Jacq.) Merr.) Menggunakan Metode BSLT - Haryanto Haryanto; Resky Aulifiyah Haswari.B; Aulya Nurul Imama R; Agung Nur Aqdi; Rahasia Rahasia; Ilmi Nurashilah; Alya Salsabila; Risya Nida Kaffyiah Sereang; Mawar Sahid (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Samanea saman (Jacq.) Merr. leaves contain various secondary metabolites with potential biological activities; therefore, preliminary toxicity testing is necessary to evaluate their safety and bioactive potential. This study aimed to determine the Lethal Concentration 50 (LC₅₀) value of the 80% ethanol extract of Samanea saman leaves using probit analysis and to classify its toxicity level. An experimental study was conducted using the Brine Shrimp Lethality Test (BSLT) with Artemia salina Leach larvae as the test organism. The extract was tested at concentrations of 10, 100, 500, 1,000, and 5,000 ppm. Larval mortality was recorded after the incubation period, and the data were analyzed using probit analysis to determine the LC₅₀ value. The results showed that larval mortality increased with increasing extract concentration, reaching 18.42%, 23.33%, 45.83%, 70.83%, and 88.89%, respectively. Probit analysis revealed an LC₅₀ value of 301.72 mg/L (ppm). Based on the toxicity classification, this value falls into the moderately toxic category, indicating that the 80% ethanol extract of Samanea saman leaves exhibits toxic activity against Artemia salina larvae. These findings suggest that the extract has promising potential as a source of bioactive compounds and warrants further investigation, including the isolation and identification of active constituents, cytotoxicity evaluation, and safety assessment in more complex biological systems.